MASLAHAH DAN KEBEBASAN DALAM FIQIH: TELAAH FILOSOFIS KONSEP MASLAHAH AL-MURSALAH PERSPEKTIF AL-GHAZALI: PROBLEMS AND FREEDOM IN Fiqih : PHILOSOPHY OF THE CONCEPT OF MASLAHAH AL-MURSALAH AL-GHAZALI'S PERSPECTIVE - Hafidz Syuhud; Kawakib (Pusat Riset dan Inovasi Nasional, 2022)
Philosophically about the concept of mashlahah al-Ghazali, is not just an effort to gain benefits or avoid mafsadat. But more than that, the real key to maslahah lies in maintaining maqashid al-syari'ah al-khamsah, namely the guarantee of safety or preservation of religion, soul, mind, lineage, and property. The meaning of freedom from the perspective of maslahah al-Ghazali is a person's mental attitude that describes a sincere and sincere acceptance in carrying out an obligation as a manifestation of his religious awareness. Freedom has absolutely nothing to do with choice, because it is a positive response from an individual in carrying out his duties as a servant of Allah, whether he chooses it or not. So the essence of freedom here is sincerity. Namely, the ability to carry out the provisions of the Shari'ah without feeling any pressure. This is the freedom of fiqhiyah, a nuance of freedom that releases a person from fear, anxiety and worry, as well as all forms of worldly 'miracle' bonds, which are born as a psychological effect of one's loyalty in carrying out divine values ​​sincerely and correctly.